The Association between Impaired Glucose Regulation and Prognosis of Chinese Patients with Intracerebral Hemorrhage - Sun, Shichao (Sci Rep, 2016)
This study aimed at observing the influence of impaired glucose regulation (IGR) on 1-year outcomes in patients with intracerebral hemorrhage (ICH). Patients hospitalized for ICH from 2008 to 2009 were recruited consecutively at 35 centres across China. A standard oral glucose tolerance test at day 14 ± 3 after stroke onset or before discharge was performed to identify IGR. The outcomes were death (modified Rankin scale [mRS] score of 6), dependency (mRS score of 2 to 5) and poor outcome (mRS score of 2 to 6) at 1 year. Cox proportion hazard model for death and logistic regression model for dependency and poor outcome were performed to investigate the influence of IGR on 1-year outcomes. A total of 288 non-diabetic ICH patients were included in this analysis, among which 150 (52.1%) were IGR. IGR was associated with 1-year dependency (adjusted odds ratio [OR] 2.18, 95% confidence interval [CI], 1.19–3.99; P = 0.01) and poor outcome (adjusted OR 2.17; 95% CI, 1.24–3.80; P = 0.007) of patients with ICH. However, IGR showed no significant association with 1-year death (adjusted hazard ratio 1.49, 95% CI, 0.60–3.67; P = 0.39). IGR was independently associated with 1-year poor outcome of ICH in Chinese patients, with more important influence on dependency than death.